Problems of nonlinear optics and acousto-optics in the curriculum of "Quantum Electronics" specialization - Manak, I.S.; Karikh, E.D. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2008)
We show the role of nonlinear and acousto-optical phenomena in optical and quantum electronics and the physics of semiconductor lasers. The examples of the use of these phenomena in the optical systems of information processing and the light generation by lasers are presented.